2020
DOI: 10.4314/rjmhs.v3i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Outcomes from Mothers with Hypertension Disorders of Pregnancy: A Retrospective Study at a Referral Hospital in Rwanda

Abstract: Background Globally, maternal hypertensive disorders in pregnancy significantly increase both maternal and perinatal morbidity and mortality. Maternal hypertension affects 14 percent of pregnancies. Eearly detection and management are critical for improving the health outcomes of both mother and neonate. Objective To assess the association between maternal hypertension disorders in pregnancy and immediate neonatal outcomes at a University Teaching Hospital in Rwanda. Methods A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
0
0
Order By: Relevance
“…The combined application of labetalol, nifedipine, and magnesium sulfate can effectively improve blood circulation and reduce the damage of hypertension to heart, kidney, and other target organs, thus improving the internal environment [ 33 , 34 ]. It is consistent with the results of Uwizeyimana et al [ 35 ] and Houehanou et al [ 36 ]. Most of the patients with PIH are in hypercoagulable state.…”
Section: Discussionsupporting
confidence: 93%
“…The combined application of labetalol, nifedipine, and magnesium sulfate can effectively improve blood circulation and reduce the damage of hypertension to heart, kidney, and other target organs, thus improving the internal environment [ 33 , 34 ]. It is consistent with the results of Uwizeyimana et al [ 35 ] and Houehanou et al [ 36 ]. Most of the patients with PIH are in hypercoagulable state.…”
Section: Discussionsupporting
confidence: 93%
“…Study done byHassan et al, (2015),Uwizeyimana et al, (2020) andGaur et al, (2021) reported that 60%, 50%, 37.8%, 39.7% of neonates respectively suffered from RDS born to mother with PIH. In our study also 9.3% neonates have RDS after the delivery.Most of the surfactant is produced up to 32-34 weeks, but as in neonate born to PIH mother there is more number of preterm delivery therefore most of the neonates have RDS after the delivery.…”
mentioning
confidence: 99%